How children develop - Siegler, Robert; Deloach, Judy ; Eisenberg, Nancy (New York, 2011)
This is an exciting time in the field of child development. The past decade has brought new theories, new ways of thinking, new areas of research, and innumer-able new findings to the field. We originally wrote How Children Develop to de-scribe this ever-improving body of knowledge of children and their development and to convey our excitement about the progress that is being made in under-standing the developmental process. We are pleased to continue this endeavor with the publication of the third edition of How Children Develop.
Keywords: Child development